Utopia e barbárie: um estudo histórico da política criminal do medo - Soares, Lúcia Dídia Lima (2018)
This study analyzes the criminal policy's concept, evolution and its relation with the humanist criminology. It seeks to understand the causes of an apparent rupture between the contemporary criminal policy and the enlightenment's principles which have guided modernity. In addition, it tries to reflect whether such a phenomenon is irreversible or whether there is room for a return of humanism. In order to do so, it addresses in the first chapter the concepts of criminal policy and humanism, and then begins to analyze the development of the main criminal policies adopted after the Social Welfare crisis in the 1970s to the present day. It should be noted that from the 1970s onwards, the gap between criminal policy and humanistic criminology began to be seen, a distance that seems to be increasing with the increasing discourses of rigor and intolerance on the political scene. Finally, in the conclusion, we present the main arguments that support this finding and suggest ways that may support a resumption of humanism. This study is current because it seeks to contribute to one of the main problems faced by contemporary societies: the containment of violence and crime efficiently but respecting human dignity.